1999
DOI: 10.1190/1.1444576
|View full text |Cite
|
Sign up to set email alerts
|

Imaging through gas‐filled sediments using marine shear‐wave data

Abstract: Marine multicomponent sea‐floor data of excellent quality have been acquired over the Tommeliten Alpha field. The most dominating wave modes are interpreted to be conventional compressional PP-waves and converted PS-waves. The most important geophysical problem associated with the Tommeliten Alpha field is the presence of a gas chimney obscuring the conventional 3-D seismic image of the reservoir zone. The converted PS-waves effectively undershoot the gas chimney, leading to substantially improved images of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…These observations were confirmed by a shear wave experiment indicating high gas-saturation within a chimney structure at Tommeliten (Granli et al, 1999). This kind of chimney is interpreted to be caused by gas saturated fractures within a low permeable cap rock (Løseth et al, 2009).…”
Section: The Nature Of Type-b-anomaliessupporting
confidence: 68%
See 2 more Smart Citations
“…These observations were confirmed by a shear wave experiment indicating high gas-saturation within a chimney structure at Tommeliten (Granli et al, 1999). This kind of chimney is interpreted to be caused by gas saturated fractures within a low permeable cap rock (Løseth et al, 2009).…”
Section: The Nature Of Type-b-anomaliessupporting
confidence: 68%
“…Based on our interpretations, 46 large-scale vertical seismic anomalies are present in the study area. Large scale chimney-like anomalies have so far been described as solitary structures (Gay et al, 2012), in many cases above leaking deep reservoirs (Hovland and Sommerville, 1985;Granli et al, 1999).…”
Section: Fluid Flow Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other conventional migration methods can be applied to PP-and PS-wavefields after their separation. Usually, the P-and S-waves can be approximated by the vertical-and horizontal-component data (Granli et al, 1999) or separated by using approximations such as elastic potentials (Etgen, 1988;Zhe and Greenhalgh, 1997;Sun and McMechan, 2001;Stanton and Sacchi, 2014). The separation of P-and S-waves is not always accurate because it will generate crosstalk artifacts between the unseparated wave modes in the migration images (Du et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PS converted-wave traveltime and velocity difference between positive and negative offset can be observed if the source and detector are interchanged for a converted wave travelling through a gas cloud, which degrades the PS converted wave imaging. Granli et al (1999) fi rst demonstrated the PS convertedwave difference when the data from Tommeliten fi eld was processed. It was named the diodic effect by Thomsen (1999).…”
Section: Introductionmentioning
confidence: 99%